Experimental Investigation of Engine Performance for 2nd Generation Biodiesel Derived from Mg2Zr5O12 Catalyst - Veena Singh; Supriya B. Chavan; Yogesh C. Sharma (Energies, 2022)
In the present study, experimental analyses were conducted by using biodiesel derived from second-generation feedstock. In terms of cost and accessibility, second-generation feedstock has gained more attention due to its environmental approach. Waste-cooking-oil-derived methyl ester was produced through a transesterification reaction in the presence of a synthesized magnesium zirconate (Mg2Zr5O12) heterogeneous catalyst. This trans-esterified waste cooking oil (WCO) was used as biodiesel and was blended with diesel in 10%, 20%, 30%, 40%, and 50% by volume ratio for further analysis. The fuel properties of pure and blended biodiesel were investigated in terms of flash point, density, kinematic viscosity, and lower heating value as per the American Society for Testing and Materials (ASTM) D-6751 standards. For each blended fuel, the engine performance and gaseous emissions trend with engine loads of 0, 3, 6, 9, and 12 kg were measured on a Kirloskar TV1 IC engine. The results indicated that the 40% blended biodiesel has the maximum brake thermal efficiency (BTE) of 19.13% and exhaust gas temperature (EGT) of 6.98% increment, also showing an increase with respect to engine load. On the other hand, brake-specific fuel consumption (BSFC) was highest for 40% blending as 36.48% increase, and that decreases with the increase in engine loads. Significant reductions in carbon monoxide (CO) and unburned hydrocarbon (HC) emissions were observed for 40% blended fuel and were 34.78% and 38.1% reduction, respectively. CO and HC emissions decreased with respect to the engine load. Meanwhile, reverse trends for carbon dioxide (CO2) and nitrogen oxide (NOx) have been observed as 14.57% and 27.85% increases for 100% biodiesel. CO2 and NOx increased with increase in engine load. The mass balance and environmental factor of crude and purified biodiesel were studied to show the environmental suitability of synthesized product. Overall, the results showed that the blended biodiesel can be used as a substitute and has an advantage over diesel fuel. The main contribution derived from this work is to improve engine performance and gaseous emission by using blended biodiesel derived from a recyclable heterogeneous catalyst and waste-cooking-oil feedstock.